2008
DOI: 10.1103/physrevd.78.045005
|View full text |Cite
|
Sign up to set email alerts
|

Chiral fermions in a spacetime with multiple warping

Abstract: In a six dimensional brane world model with multiple $S_1/Z_2$ warping, two of the 4-branes at the boundaries have coordinate dependent brane tensions in order to implement the orbifolded boundary conditions consistently. Such brane tension is shown to be equivalent to a scalar field distribution on the brane [1]. We show that in such a scenario a masslesss left chiral fermion on the 4-brane localizes naturally on the standard model 3-brane located at one edge of the compact manifold while the massless right c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…Fermions on branes have been studied in a number of articles such as in Refs. [44,45,46,47,48,49,50,51,52,53,54]. In this section let us investigate whether spin 1/2 fermions can be localized on the thick brane given in previous section.…”
Section: Fermion Localization and Resonances On The De Sitter Thmentioning
confidence: 99%
“…Fermions on branes have been studied in a number of articles such as in Refs. [44,45,46,47,48,49,50,51,52,53,54]. In this section let us investigate whether spin 1/2 fermions can be localized on the thick brane given in previous section.…”
Section: Fermion Localization and Resonances On The De Sitter Thmentioning
confidence: 99%
“…Some of these are formulated by placing the standard model fields inside the bulk. For these models the localization property of a bulk fermion field on the brane [48][49][50][51][52][53][54][55] has been a subject of great interest to explore the chiral nature of massless fermions and also the hierarchical masses of fermions among different generations [54]. In this context, it is observed that the overlap of the bulk fermion wave function on our visible brane plays a crucial role in determining the effective radion-fermion coupling, which in turn determines the phenomenology of the radion with brane matter fields.…”
Section: Introductionmentioning
confidence: 99%
“…Study of fermion and gauge fields localization on topological defects have been extensively studied with co-dimension one [20][21][22][23][24][25][26][27] and two [28][29][30][31][32][33][34][35][36][37]. Many years ago, particle localization on a domain wall in higher dimensional space time was already addressed [38,39].…”
Section: Introductionmentioning
confidence: 99%